USING A «DIRECTA» LUXATOR FOR DENTAL EXTRACTION OPERATION - Javadiasl, Afshin; Malanchuk, Vladislav; Topchii, Dmitro (The Ukrainian Scientific Medical Youth Journal, 2020)
Reducing the trauma of the operation of dental extraction and preservation of the intact bone tissue of the alveolar process of the jaw after surgery to allow subsequent dental implantation. Dental extraction operations were carried out in 60 patients for two months in the surgical depart- ment of the dental medical center of Bogomolets national medical university. 25 of patients have their teeth removed using traditional instruments – elevators and forceps, 35 patients have tooth extraction using only the «Directa» Luxator or in combination with traditional instruments. Local complications during the dental extraction by an elevator: a fracture of the tooth crown, rupture of the mucous membrane of the alveolar process, a fracture of the wall of the hole occurred in 30% of cases. The results of study indicate that by using luxator to remove teeth, the listed local com- plications were not observed. In cases of fracture of the crown of the root of the tooth, using luxator, it was possible to avoid traumatic atypical extraction of the fractured root. Reducing the time of sur- gical intervention using «Directa» Luxator compared to the use of an elevator and forceps allowed us to minimize postoperative inflammatory complications. The advantages of using luxator are: shorter time of a dental extraction operation, less traumatic damage to the periodontal and tooth cavity walls, no complications during the operation and after its completion, creating favorable conditions for car- rying out a single-stage implant after dental extraction.